Zhenskii sport v period stanovleniya sovremennogo mezhdunarodnogo olimpiiskogo dvizheniya - Myagkova, S. N. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The 2000 became rather sign for the female athletes. This year was executed equally 100 years from that moment as the women for the first time have taken part in Olympic games. It was reflected in Sydney Games, about which they have told: "The present Olympiad has female personality". The long 100 years had passed till women came to an opportunity to be equal with men participation in the sports competitions of the international scale, and to an opportunity of equal with men participation in the management of the nternational sports and Olympic movement. The aspiration to overcome the gender-role stereotypes about "the limited capabilities of women", had seriously corrected the women social status in the end of XIXth. It was expressed in the active interest of the women for the participation in the various kinds of body-motor practice. The corporal image the woman as the whole and attitude to her potential participation in the international sports and the Olympic movement is transformed to this period of time in the world tendencies of the change of the social importance the woman. The process of the integration of women in the international sports movement was slow and difficult. Its basic historical stages are stated in this paper.